Oncological Outcomes and Safety of Ovarian Preservation for Early Stage Adenocarcinoma of Cervix: A Systematic Review and Meta-Analysis - Cheng, Hongyan; Huo, Lanqing; Zong, Liju; Kong, Yujia; Yang, Junjun; Xiang, Yang (Frontiers in Oncology, 2019)
Objectives. To evaluate the oncological outcomes and safety of ovarian preservation, and to review the prognostic factors for ovarian metastases in early stage cervical adenocarcinoma. Methods. PubMed, Embase and Cochrane databases were searched for publications up to January 2019. Two investigators independently screened the studies for eligibility and extracted specific data. The primary outcomes were overall survival (OS) and progression¬-free survival (PFS). Pooled odds ratios (ORs) and 95% confidence intervals (CIs) were calculated using STATA statistical software version 19.0. Results. A total of 68 unique manuscripts were identified through the search strategy, and 10 studies were included in the meta-analysis of the safety of ovarian preservation. Fixed-effects model was used because of moderate heterogeneity. Pooled results of the included studies showed that ovarian preservation is not associated with a statistically significant OS (OR 1.00, 95% CI 0.64–1.56, I2=25.7%) or PFS (OR 0.98, 95% CI 0.57–1.66, I2=0%) in early stage cervical adenocarcinoma. In addition, 19 studies were included in the review of prognostic factors for cervical adenocarcinoma and risk factors for ovarian metastases. The incidence of ovarian metastases was 0% in stage IA, 2.8% in stage IB, 3.4% in stage IIA, and 11.8% in stage IIB cervical adenocarcinoma. cervical adenocarcinoma. International Federation of Gynecology and Obstetrics (FIGO) stage, tumor size, deep stromal invasion (DSI), lymph node metastasis (LNM), and vaginal invasion were significantly related to poor prognosis. Risk factors associated with ovarian metastases included age, FIGO stage, tumor size, DSI, parametrial invasion, corpus uteri invasion, LNM, vaginal invasion, and blood vessel invasion. Conclusions. Ovarian preservation in young patients with early stage cervical adenocarcinoma is safe and has no significant effect on OS or PFS. Preserving ovaries in patients with FIGO stage IIB seems not reasonable because of the high rate of ovarian metastasis.